Methods of bias correction - Jolly, G.M. (International Livestock Centre for Africa, 1981)
Discusses four types of correction for bias related to the spotting and counting of animals either directly or from photographs, mentioning the estimation of correction factors, regression, the use of two surveys by independent observers using either the same or different methods, and correction based on assumed distribution.